The Association of Plasma Trimethylamine N-Oxide With All-Cause and Cardiovascular Mortality: The Multi-Ethnic Study of Atherosclerosis. (7th June 2021) - Wang, Meng; Li, Xinmin; Wang, Zeneng; Otto, Marcia de Oliveira; Lemaitre, Rozenn; Fretts, Amanda; Sotoodehnia, Nona; Budoff, Matthew; Nemet, Ina; DiDonato, Joseph; McKnight, Barbara; Tang, Wilson; et al.
Abstract: Objectives: Trimethylamine N-oxide (TMAO) is a gut-microbiota generated metabolite of dietary phosphatidylcholine, choline, and carnitine. TMAO has been suggested to play a role in the pathogenesis of multiple diseases. Yet, studies of TMAO and mortality were conducted in convenience samples of patients with prevalent diseases and lacked socioeconomic and lifestyle data, raising the likelihood of selection bias and residual confounding. To address these research gaps, we investigated the associations of plasma TMAO levels with all-cause and cardiovascular disease (CVD) mortality in a prospective multi-ethnic community-based cohort. Methods: The study included 6776 participants from the Multi-Ethnic Study of Atherosclerosis. TMAO was measured at baseline using mass spectrometry. Adjudicated CVD deaths included death due to coronary heart disease, stroke, other atherosclerotic diseases, or other CVDs. Multivariable Cox proportional hazards models assessed associations with adjustment for baseline sociodemographic, lifestyle, diet, and traditional CVD risk factors (BMI, blood pressure, lipids, diabetes, CRP, medications). We also assessed pre-specified interactions by age, sex, race/ethnicity, low vs. high adherence to Alternate Healthy Eating index, and renal function measured by creatinine-based estimated glomerular filtration rate (eGFR). Results: During median follow-up of 15.9 years, 1548 participants died, 362 from CVD. Higher TMAO levels were associated with higher risk of both all-cause mortality (HR = 1.09, 95%CI: 1.04 - 1.13, per inter-quintile range increase, 7.5 µM/L) and CVD mortality (HR = 1.10, 95%CI: 1.02 - 1.19). Interaction by renal function was observed for all-cause mortality (P-interaction < 0.005), with a positive association between TMAO and risk in those with impaired renal function (eGFR < 60) [HR = 1.15, 95%CI: 1.09 -1.21], but not normal or mildly reduced renal function (eGFR ≥ 60) [HR = 1.02, 95%CI: 0.95 - 1.08]. No other significant interactions were observed. Conclusions: In this multi-ethnic community-based cohort of US adults, higher plasma TMAO levels were associated with a higher risk of all-cause and CVD mortality. The mechanisms of interaction by renal function need to be further studied, especially given that TMAO is renally cleared. Funding Sources: NIH